Marital satisfaction in deaf couples: a review study - Abedi, Arezoo; Rostami, Mohammad; Abedi, Somayeh; Sudmand, Nasrin; Movallali, Guita (Shinavāyi/shināsi-i, 2018)
Background and Aim: One of the most important aspects of marital life is the satisfaction of couples. Marital satisfaction is a positive and enjoyable attitude that the husband and wife have in different aspects of marital relations such as relationships, personality issues, conflict resolution, financial issues, sexual relations, and children. Deafness affects the relationship between couples and may decrease emotional and physical intimacy. Therefore, loss of hearing has negative consequences for marital satisfaction. This study aimed to investigate marital satisfaction in deaf couples. Recent Findings: A review of studies between 1978 and 2017 has shown that marital satisfaction in couples who are both deaf are higher than couples who one of the couples is deaf. Conclusion: Studies show that deaf- hearing marriage leads to less life satisfaction than deaf-deaf or hearing hearing marriage. Lack of national studies in this field is obvious. It seems that teaching the couples life skills by can be helpful. Keywords: Deaf; couple; marital satisfaction